Marine Quaternary dinoflagellate cysts of Australia, Papua-new guinea, New Zealand and the Southern Ocean: A review - Andrew McMinn (2002)
Dinoflagellate cysts are widespread in Australian, Papua-New Guinea, New Zealand and Southern Ocean Pleistocene and Recent marine sediments. They occur in estuaries and deltas as well as on the continental shelf and in ocean basins. They have proven invaluable in palaeoecology for the interpretation of changing temperature, salinity and distance from shore in particular. These changes have also been used to examine climate change in Quaternary sequences. A small number of First Appearance Datums (FADs) and Last Appearance Datums (LADs) within this time period allows only limited biostratigraphic definition. LADs within the Pleistocene of southern Australia include Achomosphaera ramulifera and Spiniferites rubinus. Introduction within the past 50 years of several taxa, such as Gymnodinium catenatum and Gymnodinium microreticulatum, has been attributed to ballast water import.